2019
DOI: 10.1177/0300060519867826
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection pathogens and antimicrobial susceptibilities in Kobe, Japan and Taipei, Taiwan: an international analysis

Abstract: Objective This study compared urinary tract infection (UTI) pathogens and antibiotic susceptibilities between Kobe, Japan and Taipei, Taiwan to investigate the regional resistance pattern of UTI-causative bacteria. Methods UTI-causative bacteria and antibiotic susceptibility for 4519 samples from Kobe University Hospital, Kobe and 25,131 samples from Shuang-Ho Hospital, Taipei from 2015 to 2017 were retrospectively analyzed to compare the differences between these hospitals. Results Escherichia coli was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…There were several bacterial characteristics contributing to the development of E. coli UTI, the phylogenicity, virulence factors, and antimicrobial resistance of UPEC strains varied from region to region [ 14 19 ]. The study dealing with uncomplicated community-acquired UTI in women by PFGE showed that 77% after Pivmecillinam treatment had a relapse with the primary infecting E. coli strains [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were several bacterial characteristics contributing to the development of E. coli UTI, the phylogenicity, virulence factors, and antimicrobial resistance of UPEC strains varied from region to region [ 14 19 ]. The study dealing with uncomplicated community-acquired UTI in women by PFGE showed that 77% after Pivmecillinam treatment had a relapse with the primary infecting E. coli strains [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…UTIs are the most common class of infectious disease, and antibiotics are their main means of treatment. The most common pathogen group in urine cultures is PE, which accounts for 30% to 40% of all urine culture bacteria [9]. In recent years, ESBL-PE infection has been on the rise, and it is the main cause of hospital and community-acquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ESBL-PE infection has been on the rise, and it is the main cause of hospital and community-acquired infections. In a study of antimicrobial resistance trends from 2010 to 2013, ESBL-PE was frequently detected in China and Southeast Asia, and the ESBL production rate of E. coli and K. pneumoniae in some Asian countries was as high as 60% [9]. A study by Vachvanichsanong estimated that ESBL-PE represented one-third of all E. coli and K. pneumoniae UTI episodes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus, Streptococcus pyogenes, and Enterococcus faecalis are microbes most frequently isolated from wound infections [24]. Same pathogens Escherichia coli, Klebsiella pneumoniae, and Enterococcus faecalis are prevailing in postpartum UTIs [25]. Escherichia coli, Klebsiella pneumoniae, and Streptococcus are the most frequently isolated pathogens in postpartum sepsis [26].…”
Section: Puerperal and Postpartum Infection Microbiologymentioning
confidence: 99%